KAMPUNG WISATA EKOLOGIS (KWE) PUSPA JAGAD SEBAGAI DESA WISATA (Ditinjau dari Aspek Manajemen Sumber Daya Manusia) - Arkham Maulana; Sumarji Sumarji (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
KWE Puspa Jagad is a Tourism Village in Semen Village, Gandusari District, Blitar Regency. Tourism Village is a form of integration between attractions, accommodation and supporting facilities that are presented in a community life structure that is integrated with applicable procedures and traditions. Indonesian Government has massive promote tourism now. This development reaches the lowest level, which is the village formed in the tourist village. The tourism village was formed from the utilization of the village's original potential both from economic activities, native culture and local village human resources. Empowering rural communities through tourism s a labor-intensive activity. The typical local economic and cultural activities can be presented as tourist attractions with village community guides. Tourism village HR management has supporting factors including a high level of social awareness and is easy to direct, but also has an inhibiting factor, low quality of existing human resources. As an organization at the rural level, HR management is carried out simply, following the existing HR level. Planning is limited to HR management in the tourism business development plan without increasing member. Managerial level is choiced base on the level of education and experience in the organization. Performance assessment is only based on discipline and quality of service. HR operational functions are carried out simply, following the capabilities KWE Puspa Jagad members. New members Recruitment is not held specifically, but every time native people can apply become member. HR development doing by learn from skilled organizations or other groups, attend training and autodidact. Work compensation is carried out simply by following what is common in rural areas with 3 levels: managers, trained staff and helpers. Integration is carried out by family based deliberations. Mintenance members is emphasized in providing awareness that in the KWE organization Puspa Jagad is friendship group and loving organizations able to provide added value for active members. Discipline is base on of the awareness members themselves, if undiscipline, manager will give a personal warning. Termination members of KWE Puspa Jagad isn’t done, but members who never participated in the activities are considered inactive members.